Weather Effect on Migration of Some Elements from Bottle to the Drinking Water - Al-Dayel, O.; Hefne, J.; Al-Horayess, O.; Al-Durahim, A. (Asian Journal of Chemistry, 2012)
The effect of weather on the quality of bottled drinking water is investigated. The concentration of some inorganic metals is a restrictive factor for drinking water quality, generally as consequence of their effects on the health. This fact makes necessary its regulation and monitoring. Usually drinking water bottles made of polyethylene terephthalate. Antimony concentration present in the polyethylene terephthalate is in the range of 136-190 ppm. The migration of some elements from the bottle to the water and the effect of weather in this process was monitored using inductively coupled plasma mass spectrometer technique.